Aktuelle Herausforderungen der Modellierung minimaler phänomenaler Erfahrungen (MPE) bei Thomas Metzinger. Hemisphärotomie als Fallstudie - Gauvry, Charlotte (Zeitschrift für Theologie und Philosophie, 2026)
Since 2020, Thomas Metzinger has been developing a minimalist model of "pure consciousness", known as the MPE model. This model offers significant descriptive and explanatory advantages, as it identifies minimal conditions for consciousness that are intended to be theoretically neutral and universally applicable to all cases of "consciousness as such". However, this article argues that recent candidates for minimal consciousness - particularly so-called borderline cases emerging from recent advances in neurosurgery and medical biology - pose unique challenges to this promising model. By examining one such borderline case, namely the isolated hemisphere following hemispherotomy, this article demonstrates that these challenges are primarily epistemological. This case calls into question the minimalist and universal assumptions of the MPE model. Moreover, these challenges also raise ethical concerns, especially if one accepts that entities capable of phenomenal consciousness - particularly sentience - may warrant a privileged moral status.